Course of subthreshold manic symptoms and related risk factors in the general population: A three‐year follow‐up study. (26th December 2022) - Beekman, Rosalie A. L.; ten Have, Margreet; de Graaf, Ron; Kupka, Ralph W.; Regeer, Eline J.
Abstract: Objectives: Subthreshold manic symptoms (subM) are a risk factor for the onset and recurrence of bipolar disorder (BD). Individuals with subM may benefit from preventive interventions, however, their development is hampered by a lack of knowledge on subM prevalence and subsequent course. This study examines subM characteristics, course, and risk factors for an unfavourable course. Methods: In a Dutch representative, population‐based sample aged 18–64 ( N = 4618), we assessed subM, defined as the occurrence of manic core symptoms (elation/irritability), without meeting full DSM‐IV criteria for BD I or II in the past 3 years. Comparison groups had either no manic symptoms (noM) or hypomania/mania in the context of BD (mBD) in the past 3 years. Furthermore, we differentiated a mild and moderate type of subM, based on the number of manic symptoms. A subsequent three‐year course was assessed prospectively. Results: SubM had a three‐year prevalence of 4.9%. Its prevalence, characteristics, and course were in between noM and mBD, and there were few differences between mild and moderate subM. Over the 3‐year follow‐up, 25.0% of individuals with subM had persistent subM and another 6.1% transitioned to mBD. Eleven significant risk factors for this unfavourable course were found. The most important were a history of depression/dysthymia (OR 3.75, p ≤ 0.001), living alone (OR 2.61, p ≤ 0.01) and elevated neuroticism score (OR 1.21, p ≤ 0.001). Conclusions: This study supports the validity and clinical relevance of subM as a BD prodrome. It demonstrates that subM symptoms often persist or increase during follow‐up and identifies 11 risk factors that are associated with an unfavourable course.